Fenomena Budaya Flexing dalam Kehidupan Modern: (Tafsir Makna Tabarruj Perspektif Teori Hermeneutika Fazlur Rahman) - Ali Sajjad Baaly; Khoirul Umami; Abu Bakar (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Currently, there are many phenomena that often appear in society or social media about achievements or attitudes of showing off done by someone to gain public attention. This action has similarities with the habits of the ignorant people who often show off jewelry to attract the attention of others. The term is known as Tabarruj. Based on this phenomenon, this study aims to determine the interpretation of the meaning of Tabarruj from the perspective of Fazlur Rahman's Hermeneutics theory and the Flexing phenomenon in modern life. This research is a qualitative research with a research model in the form of a literature study (Library research). The approach used in this study is a qualitative approach using several primary and secondary sources. Based on the analysis of Fazlur Rahman's Double Movement Hermeneutics Theory, Tabarruj and Flexing have the same essence, namely the behavior of showing off jewelry or body curves to attract the attention of others and the public. Although these practices were carried out at different times, the actions of Tabarruj during the ignorant period and Flexing in modern life have similar characteristics and goals. If Tabarruj was carried out in real life during the ignorant era, the Flexing phenomenon was carried out not only in real life, but also on social media platforms.